Konsep dan Praktik Literasi Informasi Untuk Mahasiswa: Kasus Mahasiswa Pekerja Paruh Waktu di UPT Perpustakaan UIN Walisongo - Bahrul Ulumi (IAIN Ponorogo, 2019)
This article reveals the pratice of information literacy done by students writing final project and working as part time workers at main library. It employs qualitattive approach which is considered the appropriate method to explore how these students implement their information skills to takle their final duties. The research shows that they partially comprehend the concept of information since they actively took part only in library orientation, as a result, they just a bit know about the concept of information ethics, although they are able to correctly finish their final works.